Safety and Efficacy of Apixaban Following Bioprosthetic Valve Replacements: A Retrospective Evaluation. (August 2021) - Ball, Kellie; Covington, Elizabeth W.
Background: Data on the use of direct oral anticoagulants in the setting of bioprosthetic valve replacements is limited.Objective: The purpose of this study was to describe outcomes among patients who underwent a bioprosthetic valve replacement and were subsequently prescribed apixaban.Methods: A retrospective cohort study was completed for inpatients at a community hospital who were prescribed apixaban following a bioprosthetic valve replacement from 2015 to 2020. Endpoints assessed included incidence of all-cause readmission and emergency visits within 3 months following valvular surgery, incidence of mortality, and all-cause major and minor bleeding. A post hoc analysis was conducted comparing outcomes among patients who underwent mitral versus aortic valve replacement, as well as patients with and without atrial fibrillation. The study was deemed exempt by hospital and university institutional review boards.Results: A total of 54 patients were included for analysis. All-cause readmission or emergency visit occurred in 33% (n = 18) of patients and the mortality rate was 6% (n = 3). A minor bleeding event was reported in 6% (n = 3) of patients and a major bleeding event was reported in 2% (n = 1) of patients. A thrombotic event was reported in 2% (n = 1) of patients.Conclusion: Within this cohort of patients requiring anticoagulation following bioprosthetic valve replacement, apixaban was safe and well-tolerated. However, more prospective data are needed to further correlate the safety and efficacy of apixaban, particularly in the setting of mitral valve replacement.